Illustrating Political Discourse: Comics and the Rohingya Refugee Crisis - Ferth Vandensteen Manaysay (IKAT: The Indonesian Journal of Southeast Asian Studies, 2019)
This article explores the possibility of examining a storytelling platform, which has largely been ignored by scholars of visual politics about Southeast Asia: comics. It particularly describes how comics can serve as a discursive mechanism for visual representation within the purview of the Rohingya refugee crisis in the region. Drawing from post-structuralism and visual discourse analysis as the theoretical and methodological basis of the research, the article considers a case of a long-form online comic’s engagement withthe refugee crisis,with particular attention to the criticisms about Aung San Suu Kyi and the bloody military campaign against the Rohingya minorities in Myanmar. By specifically looking into the text-image discourses and inter-textual components of the comics, this article attempts to demonstrate that the ability of comics to “speak” politics is still dependent on international news sources and wider debates, which shape the ways in which the comic artists are able to frame their work. In this case, the use of comics as a story-telling platform, however, also suggests the agency of refugees to be portrayed as political-security actors. Although the article generally focuses on the case of the Rohingya refugee crisis, it also draws attention to the contention that scholars of Southeast Asian visual politics can most profitably engage with other regional issues by turning their attention to the dynamic role of comics as an alternative medium and source of data towards the analysis of threat construction and political-security discourse about Southeast Asia.